1996
DOI: 10.1046/j.1365-3024.1996.d01-95.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression and secretion of ICAM‐1 during experimental infection with Trypanosoma cruzi

Abstract: In the present study we demonstrate that spleens and hearts from BALB/c mice infected with the virulent Tulahuén or the low virulent CA-I strains of Trypanosoma cruzi, contain substantially higher ICAM-1 transcripts than uninfected controls. ICAM-1 expression in heart cells was also increased in the protein level, as measured by flow cytometry, ELISA and immunohistochemistry. The adhesive receptor was observed not only on inflammatory cells but also on sarcolemma of cardiac myocytes from T. cruzi infected mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…In both the acute and the chronic stages, the myocytes within the heart were ICAM-1 positive. This finding is in agreement with our previous data of ICAM-1 expression at both protein and RNA levels using other mouse and parasite strains [18].…”
Section: Discussionsupporting
confidence: 94%
“…In both the acute and the chronic stages, the myocytes within the heart were ICAM-1 positive. This finding is in agreement with our previous data of ICAM-1 expression at both protein and RNA levels using other mouse and parasite strains [18].…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results, previous report has shown that LFA-1 + mononuclear cells are present in the inflamed myocardium of chronic chagasic patients with severe cardiomyopathy (Reis et al 1993), suggesting that at least part of these inflammatory cells are activated. Further, we bring evidence that the myocytes present enhanced ICAM-1 expression, confirming a previous report (Laucella et al 1996). Furthermore, as LFA-1/ICAM-1 interactions play a crucial role forming the immunological synapse (Camacho et al 2001), ICAM-1 + myocytes could be targets for LFA-1 + cytotoxic T-cells, contributing to heart dysfunction.…”
Section: T Cruzi-infectedsupporting
confidence: 90%
“…Moreover, ICAM-1 ϩ and VCAM-1 ϩ blood vessels were associated with the presence of CD8 ϩ -infiltrating T cells in the cardiac tissue of chagasic patients with severe cardiomyopathy (38). In addition, cardiomyocytes express ICAM-1 during the acute phase of experimental T. cruzi infection (27,30). Considering that ICAM-1-mediated interactions plays a crucial role in forming the immunological synapse (29,39), ICAM-1 ϩ myocytes could be targets for LFA-1 ϩ cytotoxic T cells, contributing to heart dysfunction during chagasic myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR products were separated by acrylamide gel electrophoresis and stained with silver nitrate. The primers sequences and PCR product sizes have bee n published elsewhere (30).…”
Section: Icam-1 Mrna Detectionmentioning
confidence: 99%